Development of the mathematical model for the choice of the optimal cutting condition with combined axial tool - Степанов, Михаил Сергеевич; Иванова, Марина Сергеевна (Technology audit and production reserves, 2015)
Analysis of the literature showed that the issue of determining the optimum cutting conditions when processing a combined axial tool is not considered carefully enough. In this regard, in order to increase productivity and ensure the required quality of processing holes in hydraulic and pneumatic valves by combined axial tool were developed and solved the three one-criterion problem with the corresponding evaluation function: the standard deviation of the average speed of cutting; the standard deviation of the feed per revolution; processing time. The simulation results in the system MathCAD shown that the most productive cutting conditions is obtained by the function of maximum performance. The results for the one-criterion tasks suggest that there is potentially solution that satisfies all three evaluation functions, so that it was proposed to solve the problem of rational choice of cutting conditions for combined tools as minimax problem with restrictions, including three previously proposed estimators.